2009
DOI: 10.1038/nn.2405
|View full text |Cite
|
Sign up to set email alerts
|

CREB regulates excitability and the allocation of memory to subsets of neurons in the amygdala

Abstract: The mechanisms that determine how information is allocated to specific regions and cells in the brain are fundamentally important for memory capacity, storage and retrieval, but are poorly understood. Here, we manipulated CREB in a subset of lateral amygdala (LA) neurons with a modified Herpes Simplex Virus (HSV), and reversibly inactivated transfected neurons with the Drosophila allatostatin G-protein-coupled receptor (AlstR)/ligand system. We found that inactivation of the HSV-CREB subpopulation of neurons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
489
3
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 465 publications
(535 citation statements)
references
References 43 publications
(66 reference statements)
39
489
3
4
Order By: Relevance
“…Extensive studies have shown that CREB is not only a requirement but also a critical driving force for the consolidation of long‐term conditioned fear memories (Bourtchuladze et al ., 1994; Kida et al ., 2002; Viosca et al ., 2009; Zhou et al ., 2009). We investigated whether decreased PKA‐CREB signaling induced by decreased O‐GlcNAcylation affects auditory fear conditioning in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive studies have shown that CREB is not only a requirement but also a critical driving force for the consolidation of long‐term conditioned fear memories (Bourtchuladze et al ., 1994; Kida et al ., 2002; Viosca et al ., 2009; Zhou et al ., 2009). We investigated whether decreased PKA‐CREB signaling induced by decreased O‐GlcNAcylation affects auditory fear conditioning in mice.…”
Section: Resultsmentioning
confidence: 99%
“…We (Han et al, 2007(Han et al, , 2009Yiu et al, 2014) and others (Zhou et al, 2009;Gouty-Colomer et al, 2016), previously examined how neurons in the lateral nucleus of the amygdala (LA) are allocated to an engram supporting a discrete cue fear memory (in which an initially motivationally neutral auditory cue is paired with an aversive foot shock) (Davis, 1992;LeDoux, 2000;Maren, 2003). Increasing the function of the transcription factor CREB (Ca 2+ /cAMP response element-binding protein) in individual principal LA neurons increased the likelihood that a particular neuron would become part of a fear/threat memory engram (Han et al, 2007(Han et al, , 2009Zhou et al, 2009). Furthermore, genetic ablation or suppression of LA neurons overexpressing CREB (and not an equal number of random LA neurons) impaired memory expression (Han et al, 2009;Zhou et al, 2009).…”
Section: Introductionmentioning
confidence: 89%
“…Research focusing on other brain regions show that a neuron's participation in a given engram may be biased experimentally by manipulating its intrinsic excitability (Han et al, 2009;Zhou et al, 2009;Sano et al, 2014;Yiu et al, 2014). However, it is unknown whether the same rules of allocation apply to the DG.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations